Resultados Perinatales De Hijos De Madres Adolescentes, Comparados Con Hijos De Madres No Adolescentes En Un Hospital De Segundo Nivel En México - Vega-Malagón, Genaro; De Icaza-Llera, Tannia; Becerril-Santos, Alma; Ávila-Morales, Javier (European Scientific Journal, ESJ, 2016)
OBJECTIVE: To determine perinatal outcomes of children of adolescent mothers against the ones of children of non-adolescent mothers in a second level class hospital in Mexico. METHODOLOGY: Case-control studies applied at “Hospital del Niño y la Mujer” from the National Health Department of Queretaro, Qro. from September 1st, 2015 to January 30th, 2016. A sample of 60 medical records of teenage pregnant women was studied. In addition to 90 medical records of women between 20 to 35 years old who had an obstetric event. The analysis was performed using descriptive and inferential statistics. With a 95% confidence interval and a value of p < 0.05. RESULTS: The average age range was 17.38 and 25.33 respectively. The quantitative variables, statistically significant with a p<0.05, were: weight and Apgar score one minute after birth, whereas in weeks of gestation, height and Apgar score five minutes after birth and after days of hospitalization, there was no change. The most frequent qualitative variables among adolescent women were: complications during childbirth (15%), complications with the newborn (18.3%), and route of termination of pregnancy by caesarean section (70%), while in pregnant women between 20 to 35 years old, the complications during the pregnancy were more frequent (51.1%). CONCLUSIONS: Pregnancy among adolescent women continues to have a higher mortality rate than in 20 to 35 year-old women, although it is less frequent than in previous years. It is necessary to promote sexual education to reduce the incidence in this age group.